Keteladanan Seorang Dai Dan Pengaruhnya Terhadap Akhlak Anggota Majlis Ta’lim - Ahmad Rofi; Farihatul Fitriyah (STID DI AL-HIKMAH, 2017)
This study aims to determine keteladan a preacher and an influence on the morals member taklim. The method used is qualitative descriptive approach. Research instrument used was a questionnaire and interviews. Questionnaire addressed to the congregation or the respondent. Interviews were conducted to the board of the Ar-Risala Taklim Assembly and conducted by observing the state of the environment taklim and existence. The conclusion is keteladan a preacher and influence terhadp Assembly members Taklim Ar-Risala good in a particular category.